Composição química e benefícios nutricionais dos caroços de açaí (Euterpe precatória), guaraná (Paulínia cupana) e tucumã ( Astrocaryum aculeatum)na alimentação animal. - Maia, Evandrícia dos Santos (Brasil, 2022)
The Amazon region is characterized by the availability of fruits with potential economic and nutritional. This work aimed to analyze the composition chemistry of three fruits from the Amazon region: açaí (Euterpe precatory Mart.), guarana (Paullinia cupana var. sorbilis) and tucumã (Astrocaryum aculeatum G. Meyer) and verify its importance for animal nutrition. The samples were processed at the Laboratory of Materials of the Amazon and Composites, at the of Technology at the Federal University of Amazonas, Campus Manaus. Were Moisture, ash content, Thermogravimetry and XRF analyzes were performed (X-Ray fluorescence) from açaí seeds, guarana bushes, seed whole tucumã, the endocarp of the tucumã pit and the kernel of the tucumã pit. tucumã. The moisture contents found were 9.65%, 9.09%, 7.9%, 9.34% and 6.38% and the ash contents were 22.24%, 25.80%, 20.96%, 27.46% and 10.02% for açaí seed, guarana bush, tucumã seed, tucumã endocarp and tucumã almond respectively. Therefore, these residues are rich in minerals. The main elements found in açaí seeds were K and Ca, in the guaraná bush, they were Ca and Si, in the tucumã seeds, they were K and Ca, in the tucumã endocarp were K and Ca and in tucumã almonds they were K and Ca. compounds with the highest content for açaí seeds were SiO2 and K2O, for guarana bushings were SO3 and CaO, for tucumã seeds were SiO2 and K20, for tucumã endocarp were SiO2, CaO and P2O5 and for tucumã almonds were SO3 and K20. Knowledge of chemical elements and oxides in the composition residues are of great importance for animal nutrition, enabling the sustainable management of these fruits in nature, as well as nutritional indicators such as potassium, calcium, silicon, iron and phosphorus for the formulation of animal feed. You chemical elements present in açaí, guarana and tucumã have minerals and nutrients that are important for poultry, swine, ruminant and fish nutrition. Keywords: Chemical compounds, Amazonian fruits, residues